Electronic structure of Fe/MgO/Fe multilayer stack by X-ray magnetic circular dichroism - Gautam, Sanjeev; Asokan, Kandasami; Singh, Jitendra Pal; Chang, Fan-Hsiu; Lin, Hong-Ji; Chae, Keun Hwa (AMER INST PHYSICS, 2014)
The interface properties of Fe/MgO/Fe multilayer stack were investigated by using X-ray absorption spectroscopy (XAS) and X-ray magnetic circular dichroism (XMCD). The magnetic multilayers were deposited by electron beam evaporation method, which exhibits the attributes of perpendicular magnetic anisotropy (PMA). XAS analysis shows that Fe-layer forms a Fe-O-rich interface region with MgO-layer and a sum-rule analysis of the XMCD estimates the average magnetic moment of 2.31 +/- 0.1 mu(B) per Fe-atom. XAS and XMCD studies indicate the formation of a heterostructure (Fe/FeO/Fe2O3) on the interface. A phase transition in Fe-O stoichiometry at interface is also observed at low temperature (90 K), which may be useful in magnetic storage technology. (C) 2014 AIP Publishing
Keywords: TRANSITION-METAL COMPOUNDS; 2P ABSORPTION-SPECTRA; ROOM-TEMPERATURE; LAYERS; SPECTROSCOPY; JUNCTIONS; FERRITE; SI(111); COBALT; FILMS